From labor to cash flow? The abolition of immigration restrictions and the performance of Swiss firms - Jan Ruffner; Michael Siegenthaler (ETH Zurich, KOF Swiss Economic Institute, 2016)
What is the effect of opening the labor market to foreign workers on the success of firms? We address this question by analyzing how firms in Switzerland were affected by the introduction of the free movement of persons with the European Union (EU) countries. This immigration reform granted all EU workers free access to the Swiss labor market. Our firm-level panel data models exploit the exceptional facts that the reform incidentally affected firms at different time periods and had a stronger effect on firms close to the border. We find that the reform increased employment, skill intensity, and sales of incumbent firms, especially for those that relied heavily on foreign workers and had reported that they suffered from skill shortages before the reform. In these firms, the reform also increased labor productivity. We explain these effects through the higher innovation performance of incumbent firms and the reallocation of economic activity into highly affected regions, as evidenced by the entry of new establishments and by the changes in establishment size within multi-establishment firms.
Keywords: J22; J61; F22; 330; skilled immigration; immigration policy; free movement of persons; immigration restrictions; firm performance; labor mobility; firm relocation